Ethnobotanical Study of Medicinal Plants Used by Local Population of Ilam City on Back Pain, West of Iran - Damoun Razmjoue; Mohammad Ezati; Naser Abbasi; Mohadeseh Pirhadi; Behnaz Shojaei; Mahmoud Bahmani (Tehran University of Medical Sciences, 2024)
The diverse geographical regions of Iran have tribes with different cultures and customs in the medicinal use of plants in the control, prevention and treatment of diseases, and on this basis, to collect valuable ethnobotanical information in the field of medicinal plants, more studies are needed among different tribes. It is so that in the event of the death of people with this knowledge, their historical and experimental knowledge will not be forgotten. In this ethnobotanical and systematic study in the city of Ilam (western Iran), an attempt has been made to identify and report the use of medicinal plants native to this region in the treatment of back pain. Traditional therapeutic information about medicinal plants effective on back pain is done by ethnobotanical questionnaire. The complete list of herbal druggists in Ilam city was obtained from the Food and Drugs deputy, and the interviewer collected the required information personally by visiting each and every herbal druggists in Ilam city. The questionnaire included personal information and the names of native plants, the organ used, the method of use, and the effect of traditional treatment for back pain. Data analysis shows that 16 medicinal plants from 15 plant families are used in the treatment of back pain in Ilam. Medicinal plants Pistacia khinjuk, Amygdalus communis, Achillea biebersteinii, Amygdalus arabica, Pistacia atlantica, Thymbra spicata, Capsicum annuum, Biebersteinia multifida, Nigella sativa, Salvia rosmarinus, Hypericum helianthemoides, Calendula persica, Citrullus colocynthis, Zingiber officinale, Elaeagnus angustifolia, Nerium oleander, Myrtus communis and Ricinus communis are medicinal plants that are used in Ilam city to treat back pain. Based on the obtained results, it was found that the medicinal plant Achillea biebersteinii with usage report index (UR) of 14, relative frequency of citation (RFC) of 0.73 and percentage of frequency of use (PFU) of 53.8% is the most used in the treatment of back pain. Asteraceae plant family is the most used plant family. Leaf with 37% was the most used organ and decoction with 35% was the most traditional way of use. The presence of rich plant flora and medicinal species in Ilam city provides a suitable field for pharmacological research for better use and production of medicines and herbal products against back pain.